2020
DOI: 10.1080/15248372.2020.1802277
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Processing of Nouns and Verbs at 36 Months of Age Predicts Concurrent and Later Vocabulary and School Readiness

Abstract: Children's lexical processing speed at 18 to 25 months of age has been linked to concurrent and later language abilities. In the current study, we extend this finding to children aged 36 months. Children (N = 126) participated in a lexical processing task in which they viewed two static images on noun trials (e.g., an ear of corn and a hat), or two dynamic video clips on verb trials (e.g., a woman stretching and the same woman clapping), and heard an auditory prompt labeling one of them (e.g., "Where is she st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Instead, a broader conception of processing speed which encompasses the psycholinguistic and neural mechanics of pragmatic processing (as probed in our contrastive inference task) may be a more appropriate measure. Indeed, a recent study on the relationship between processing speed, vocabulary size, and subsequent vocabulary growth reveals a complex, dynamic, and variable interaction (Peter et al, 2019; see also Koenig, Arunachalam, & Saudino, 2020). Future work investigating the drivers of pragmatic inferencing should take this complexity into account.…”
Section: Drivers Of Contrastive Inferencing Abilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Instead, a broader conception of processing speed which encompasses the psycholinguistic and neural mechanics of pragmatic processing (as probed in our contrastive inference task) may be a more appropriate measure. Indeed, a recent study on the relationship between processing speed, vocabulary size, and subsequent vocabulary growth reveals a complex, dynamic, and variable interaction (Peter et al, 2019; see also Koenig, Arunachalam, & Saudino, 2020). Future work investigating the drivers of pragmatic inferencing should take this complexity into account.…”
Section: Drivers Of Contrastive Inferencing Abilitymentioning
confidence: 97%
“…Relatedly, we would welcome studies that test our findings in less controlled environments, e.g., during shared reading or free play. Because lab-based processing in preschoolers correlates well with vocabulary (Koenig et al, 2020), we would expect our results to generalise as long as the extra time affordances were retained.…”
Section: Future Directionsmentioning
confidence: 99%
“…Indeed, Valleau et al (11) found no association between latency and vocabulary size in typically developing children under two years of age for verbs and dynamic scenes. However, age may also be a factor: Koenig et al (16) found that, for typically developing three-year-olds, latency correlated with vocabulary size on both noun and verb trials.…”
Section: Processing Speedmentioning
confidence: 99%
“…To begin to address these foundational gaps in our understanding of how eye gaze can be used to examine receptive verb vocabulary in children with language delays and disorders, we present two experiments that adapt tasks used by Valleau et al (11) and Koenig et al (16). Our goal is to explore how accuracy and processing speed measures may be adapted to accurately capture verb knowledge in children with language delays and disorders.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation